PENYULUHAN HUKUM TENTANG PENDIDIKAN HUKUM TERKAIT HAK PRIBADI DALAM BERMEDIA SOSIAL BAGI MASYARAKAT Di DESA TUGU JAYA, KECAMATAN CIGOMBONG, KABUPATEN BOGOR, JAWA BARAT - Susetio, Wasis; Lisasih, Nin Yasmine; Azis, Rizka Amelia; Hartadi, I Gede; Arianto, Henry; Olivia, Fitria; Wasahua, Idris; Saragih, Horadin; Slamet, Sri Redjeki; Ahmad, Ahluddin Saiful; Suprayogi, Agus; Muliawan, Anatomi; Feriza, Gousta; Juanda, Juanda (Universitas Esa Unggul, 2026)
AbstractThe rapid development of digital technology and social media has brought significant changes to patterns of communication and social interaction. On the one hand, social media provides a space for participation and freedom of expression; on the other hand, it also gives rise to various legal issues, particularly those related to personal rights, privacy protection, defamation, and the misuse of personal data. Low levels of digital legal literacy have made communities, especially those in rural areas, vulnerable to becoming both victims and perpetrators of legal violations in cyberspace. This Community Service Program (PkM) was conducted by lecturers of the Faculty of Law, Universitas Esa Unggul, in Tugu Jaya Village, Cigombong District, Bogor Regency, West Java, on 6–7 December 2025. The program aimed to provide legal education on personal rights in the use of social media, to enhance public legal awareness, and to encourage responsible and law-abiding social media behavior. The methods employed included lectures and socialization sessions, discussions and question-and-answer activities, as well as educational games and the distribution of rewards, with reference to Law Number 27 of 2022 on Personal Data Protection, Law Number 19 of 2016 on Electronic Information and Transactions, and relevant provisions of the Indonesian Civil Code and Criminal Code. The results of the program indicate an improvement in community understanding of the right to privacy, digital ethics, and the legal consequences of the misuse of social media. The activity also fostered preventive awareness among community members in protecting personal data and avoiding legal conflicts in the digital space. Therefore, digital legal education serves as an important instrument in building a legally competent and responsible society in the era of social media.Keywords: personal rights, social media, legal education, community service, data protection. AbstrakPerkembangan teknologi digital dan media sosial telah membawa perubahan signifikan dalam pola komunikasi dan interaksi masyarakat. Di satu sisi, media sosial membuka ruang partisipasi dan kebebasan berekspresi, namun di sisi lain juga menimbulkan berbagai persoalan hukum, khususnya yang berkaitan dengan hak pribadi, perlindungan privasi, pencemaran nama baik, serta penyalahgunaan data pribadi. Rendahnya literasi hukum digital menyebabkan masyarakat, terutama di wilayah pedesaan, rentan menjadi korban maupun pelaku pelanggaran hukum di ruang siber. Kegiatan Pengabdian kepada Masyarakat (PkM) ini dilaksanakan oleh Dosen Fakultas Hukum Universitas Esa Unggul di Desa Tugu Jaya, Kecamatan Cigombong, Kabupaten Bogor, Jawa Barat, pada tanggal 6–7 Desember 2025. Tujuan kegiatan adalah memberikan pendidikan hukum mengenai hak pribadi dalam bermedia sosial, meningkatkan kesadaran hukum masyarakat, serta mendorong perilaku bermedia sosial yang bertanggung jawab dan sesuai dengan ketentuan hukum. Metode yang digunakan meliputi paparan berikut sosialisasi, diskusi dan tanya jawab serta permainan edukatif dan pemberian hadiah yang mengacu pada Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi, Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik, serta ketentuan relevan dalam KUHPerdata dan KUHP. Hasil kegiatan menunjukkan adanya peningkatan pemahaman masyarakat mengenai hak atas privasi, etika digital, serta konsekuensi hukum dari penyalahgunaan media sosial. Kegiatan ini juga mendorong kesadaran preventif masyarakat dalam melindungi data pribadi dan menghindari konflik hukum di ruang digital. Dengan demikian, pendidikan hukum digital menjadi instrumen penting dalam membangun masyarakat yang cakap hukum dan bertanggung jawab di era media sosial. Kata kunci: hak pribadi, media sosial, pendidikan hukum, pengabdian masyarakat, perlindungan data